Rationalism in Public Law. Issue 4 (1st July 2013) - Gee, Graham; Webber, Grégoire
<x xml:space="preserve">Abstract</x> Rationalism is 'the stylistic criterion of all respectable politics'. So lamented political philosopher Michael Oakeshott in a series of essays published in the 1940s and 1950s. Rationalism, for Oakeshott, is shorthand for a propensity to prioritise the universal over the local, the uniform over the particular and, ultimately, principle over practice. It culminates in the triumph of abstract principles over practical knowledge in a manner that erodes our ability to engage in political activity. Although Oakeshott's critique was made with the practice and study of politics in mind, it has a wider relevance. Rationalism, as we see it, has become the dominant style in public law. We draw upon Oakeshott's critique to elucidate the risks associated with rationalism in public law and call for a renewed engagement with practical knowledge in the study of the constitution.